PEMBERDAYAAN KADER DALAM PERTOLONGAN PERTAMA STROKE DENGAN DETEKSI DINI FAST (FACE, ARM, SPEECH, TIME) PADA AGREGAT DEWASA DI DESA PELEM - hayati, farida (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Empowerment is a process to give or support to weaker organizations and reduce support to stronger organizations so that balance occurs. The goal of mass empowerment is to create a more favorable environment for people to live in, which will also contribute to a more favorable quality of life for people. This exercise is carried out using a material demonstration method with a sample size of 20 people. The results of the activities before the educational intervention was carried out found an average score of 73,50 and after the educational intervention was given an average score of 79,50. As a result, based on the results of the preliminary research conducted before and after the first stroke patient was treated with the FAST (Face, Arm, Speech, Time) detection method, it was determined that public awareness of the first stroke patient had increased. Detecting FAST is one method for detecting strokes that patients experience by looking at their wajah, elbow, and leg muscles, as well as their bicara sensitivity. It also involves quickly referring patients to the closest RS so they don't miss the golden period of stroke.